Characteristics of Metallo-β-Lactamase-Producing Pseudomonas aeruginosa in Korea - Hong, Jun Sung (Infect Chemother, 2015)
BACKGROUND: The aim of this study was to investigate the molecular epidemiological characteristics of metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa clinical isolates in Korea. MATERIALS AND METHODS: Three hundred and twenty nine P. aeruginosa clinical isolates were collected from 23 general hospitals in Korea from March to June 2014. Species were identified by matrix-assited laser desorption/ionization-time of flight and 16S rRNA sequencing. Antimicrobial susceptibility was determined by disk diffusion methods. Further, minimum inhibitory concentrations of carbapenems were determined by Etest. Polymerase chain reaction and sequencing were performed to identify genes encoding MBLs. Multi-locus sequence typing and pulsed-field gel electrophoresis were performed to determine epidemiological characteristics of MBL-producing P. aeruginosa isolates. RESULTS: Of the 329 isolates, 229 (69.6%) were susceptible to the carbapenems tested, including imipenem and meropenem; while 100 (30.4%) were non-susceptible to more than one of the carbapenems. Genes encoding imipenemase-6 (IMP-6) and Verona imipenemase-2 (VIM-2) MBLs were identified in 21 (6.4%) isolates (n = 17 and 4, respectively). All MBL-producing isolates showed multi-drug resistant phenotype, and a majority (n = 19) of the isolates were identified as sequence type 235 (ST235). The remaining isolates (n = 2) were identified as ST309 and ST463. CONCLUSION: P. aeruginosa ST235 might play an important role in dissemination of MBL genes in Korea.